PHYTOSYNTHESIS OF SILVER NANOPARTICLES USING E. CAMALDULENSIS LEAF EXTRACT AND THEIR CHARACTERIZATION - BASHIR,TABASSUM (Sociedad Chilena de Química, 2015)
Herein, we report a simple green synthesis of silver nanoparticles (Ag NPs) by the reduction of aqueous silver salt solution using leaf broth of Eucalyptus camaldulensis. The profile of synthesized silver nanoparticles was evaluated by using UV-visible spectrophotometer, X-ray diffractometer, atomic force microscope, energy-dispersive X-ray spectroscope and scanning electron microscope. Surface plasmon resonance peak of silver nanoparticles appeared at 425 nm in UV-vis spectra of silver nanoparticles. XRD studies clearly confirmed the crystalline nature of the synthesized nanoparticles. The EDX analysis disclosed the arranged inorganic composition of the synthesized Ag NPs. Atomic force microscopy investigation revealed 3D surface profile of nanoparticles. From the SEM images, the silver nanoparticles were found to be more or less spherical with an average diameter range of 110-250 nanometers.